Same same, but different: Word and sentence reading in German and English - Rau, A; Moll, K; Moeller, K; Huber, S; Snowling, M; Landerl, K (Taylor and Francis, 2016)
The current study compared eye fixation patterns during word and sentence processing in a consistent and an inconsistent alphabetic orthography. German and English children as well as adults matched on word reading ability read matched sentences while their eye fixation behavior was recorded. Results indicated that German children read in a more small-unit plodder-like style with more diligent first-pass reading and less re-reading. In contrast, English children read in a more large-unit explorer-like style with a greater tendency to skip words, and more regressions. Importantly, these cross-linguistic processing differences largely persisted in the adult readers. Orthographic consistency thus influences both local word recognition and global sentence processing, indeveloping and skilled readers.